Alarm System and Suitcase Tracker with Arduino Microcontroller Based on the Internet of Things - Prihandono, Yudi Renaldi; Baswara, Ahmad Raditya Cahya (Signal and Image Processing Letters, 2022)
Suitcases are prone to criminal crimes, because suitcases are a place to store valuables, especially when traveling. It is difficult to track the availability of suitcases because there are too many of the same suitcases. Research on the manufacture of alarm tools and suitcase trackers is intended to design and build a luggage tracking system using GPS, SIM 800L, Buzzer, Li-Ion 18650 Battery, and Arduino Nano which can provide alerts through smartphones connected to IoT. To find out how the system works well, testing is carried out by measuring the length of time it takes for alarm devices and suitcase trackers to track and the time it takes for the alarm to sound. The successful design of an alarm and suitcase tracker using GPS, SIM 800L, Buzzer, IoT, Li-Ion 18650 Battery, and Arduino Nano. GPS devices can lock signals with an accuracy of 98.53% for operator one and by 35.59% for operator two in a closed room state, by 97.71% for operator one, and by 62.85% for operator two in an open room state. The phone delay time with buzzer has an average delay time value of 14 seconds for operator one and 16.4 seconds for operator two and an accuracy value of 98.78%. Thus using operator one is more efficient than operator two.